Active control of foams by physically based destruction mechanisms - McHardy, Christopher; Thünnesen, Julian; Horneber, Tobias; Kostova, Jordanka; Hussein, Mohamed; Delgado, Antonio; Rauh, Cornelia (Proceedings in Applied Mathematics and Mechanics, 2018)
Foams may be undesired in technical processes and need, thus, to be actively controlled. In food science engineering it is often not possible to apply chemical measures due to the required purity of the processed products. To overcome this challenge it is necessary to apply physically based foam destruction mechanisms. The present contribution deals with the prediction of foamability and the application of acoustical foam destruction from an experimental point of view. The results show that it is possible to classify the foamability of different fluids by a correlation of dimensionless numbers containing purely physico‐chemical properties (i.e. density, surface tension, viscosity). The foam stability is a consequence of the net balance of the foam generation and the foam decay. The respective time scales may be influenced by the process conditions, the fluid properties, and the selected physically based destruction mechanism. In the case of resonance excitation of foam bubbles by acoustic waves of defined frequencies selective foam destruction can be achieved. The bubbles in the foam start to oscillate and absorb energy depending on the bubble size, fluid properties, and ultrasound frequency. The resulting bubble breakdown leads to a shortening of the time scales of the foam deca